Your Investor Blind Spots - Peterson, Richard L. (John Wiley & Sons, Incorporated, 2011)
investor. Richard and Frank's book on dealing with fear and building your investor identity is designed to tilt the odds and is a must-read for all investors." âOliver Murray, President and Chief Executive Officer, Brandes Investment Partners & Co
Description based on publisher supplied metadata and other sources
Keywords: Psychologie; Finance, Personal; Investments -- Psychological aspects; Investments